TRANSLATION AS A COGNITIVE STRATEGY FOR LIFELONG LEARNING - Kavaliauskienė, Galina; Kaminskienė, Ligija (Vertimo studijos, 2017)
Learning strategies are immensely ambiguous phenomena and nothing is clear-cut about them.Zoltan DőrnyeiThe object of education is to prepare the young to educate themselves throughout their lives. Robert M. Hutchins